Aktualisasi Konsep Khidmah di Pondok Pesantren (Studi kasus di Pondok Pesantren Al-Mardliyah Bahrul Ulum Tambakberas Jombang) - Muhammad Shalahuddin; Moh Irmawan Jauhari; Ahmad Ali Riyadi (Universitas Islam Tribakti Lirboyo Kediri, 2025)
Pesantren is an Islamic educational institution popular in Indonesia. Distinctive traditions such as mutual cooperation, communal work (ro’an), and khidmah to the kiai are deeply embedded in pesantren culture. Khidmah refers to the devotion of students to their kiai as a form of respect for the knowledge and guidance imparted. This study employs a qualitative method with a sociological-phenomenological approach and was conducted at Pondok Pesantren Al-Mardliyah. The findings reveal that khidmah in this pesantren serves as a form of worship, devotion, care for the pesantren, and a medium for applying knowledge. Philosophically, khidmah means serving and dedicating oneself to the kiai and pesantren. The concept of khidmah in this pesantren is categorized into two: 1) Salaf, khidmah as worship and devotion, and 2) Khalaf, khidmah as an expression of gratitude, care, and a platform for practicing knowledge. Khidmah remains a unique and deeply rooted tradition in pesantren.